Adaptive Deep Brain Stimulation for Parkinson's disease: Safety and effectiveness. Issue 1 (January 2019) - Bocci, T.; Arlotti, M.; Marceglia, S.; Prenassi, M.; Ardolino, G.; Cogiamanian, F.; Borrellini, L.; Rampini, P.; Locatelli, M.; Barbieri, S.; Priori, A.
Abstract : Deep Brain Stimulation (DBS) is an effective therapy for Parkinson's disease (PD). We assessed the effectiveness of adaptive DBS (aDBS), that uses beta-band power of the subthalamic Local Field Potentials (LFPs) as target to adapt DBS parameters to motor fluctuations. In a first experiment, aDBS plus levodopa versus levodopa alone was studied; in a second phase, we evaluated aDBS versus cDBS. The experiments took place 5 days after implantation and lasted 2 days (Day 5 and 6, eight hours per day). Changes in the Unified Parkinson's Disease Rating Scale (UPDRSIII) and Rush Dyskinesia Rating Scale were assessed. In the first experiment, in Day 5 DBS was turned OFF, while in Day 6 aDBS stimulation was turned on. In the second, cDBS was turned ON during Day 5 and aDBS turned ON during Day 6. aDBS improved UPDRSIII score compared to levodopa (three-way ANOVA, "day"x"medication" p = 0.003). Rush-DRS score from baseline was lower in aDBS patients than in cDBS (Wilcoxon-Mann-Whitney test: p < 0.005), although UPDRSIII was comparable (UPDRSIII mean variation, Day 5: 55.69 ± 5.16%; Day 6: 42.66 ± 4.14%). aDBS was effective in controlling the patients PD symptoms in addition to the normal Levodopa therapy, reducing dyskinesias compared to cDBS.